SURVIVING STIGMA: EXPLORING THE DOUBLE BURDEN OF WOMEN WITH DISABILITIES AND THEIR COPING MECHANISMS - Hidayatullah, Hengki Tri; Setiyowati, Arbin Janu (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Women with disabilities are often victims of discrimination and are even more marginalized compared to men with disabilities. The double burden represents a severe challenge experienced by women with disabilities. This study aims to (1) explore the double burden faced by women with disabilities and (2) identify appropriate coping strategies. The research method employed is a Systematic Literature Review, with women with disabilities as the primary focus. Following the inclusion process and quality appraisal (Appraising the Quality of Studies), a total of 19 studies were reviewed. The findings indicate that (1) the double burden experienced by women with disabilities arises from sociological pressures (family, community, and government policies) and psychological burdens in the form of emotional responses (feelings of worry, loneliness, and self-isolation) triggered by these sociological pressures. (2) The coping strategies that can be employed include emotion-focused coping and problem-focused coping. Another finding highlights the need for further research using quantitative methods to obtain more concrete results regarding the double burden of women with disabilities. The results of this study may serve as a foundation for more in-depth and representative research on the double burden faced by women with disabilities.